On the phantom-like appearance of bilingualism effects on neurocognition: (How) should we proceed?. Issue 1 (22nd January 2021) - Leivada, Evelina; Westergaard, Marit; Duñabeitia, Jon Andoni; Rothman, Jason
Abstract: Numerous studies have argued that bilingualism has effects on cognitive functions. Recently, in light of increasingly mixed empirical results, this claim has been challenged. One might ponder if there is enough evidence to justify a cessation to future research on the topic or, alternatively, how the field could proceed to better understand the phantom-like appearance of bilingual effects. Herein, we attempt to frame this appearance at the crossroads of several factors such as the heterogeneity of the term 'bilingual', sample size effects, task effects, and the complex dynamics between an early publication bias that favours positive results and the subsequent Proteus phenomenon. We conclude that any definitive claim on the topic is premature and that research must continue, albeit in a modified way. To this effect, we offer a path forward for future multi-lab work that should provide clearer answers to whether bilingualism has neurocognitive effects, and if so, under what conditions.